The Emerging Role of Fatty Acid Synthase in Hypoxia-Induced Pulmonary Hypertensive Mouse Energy Metabolism. (18th August 2021) - Hou, Cuilan; Chen, Juan; Zhao, Yuqi; Niu, Yanhua; Lin, Shujia; Chen, Shun; Zong, Yanfang; Sun, Xiaomin; Xie, Lijian; Xiao, Tingting
Abstract : Aims . This study is aimed at examining whether fatty acid synthase ( FAS ) can regulate mitochondrial function in hypoxia-induced pulmonary arterial hypertension (PAH) and its related mechanism. Results . The expression of FAS significantly increased in the lung tissue of mice with hypoxia-induced PAH, and its pharmacological inhibition by C75 ameliorated right ventricle cardiac function as revealed by echocardiographic analysis. Based on transmission electron microscopy and Seahorse assays, the mitochondrial function of mice with hypoxia was abnormal but was partially reversed after C75 injection. In vitro studies also showed an increase in the expression of FAS in hypoxia-induced human pulmonary artery smooth muscle cells (HPASMCs), which could be attenuated by FAS shRNA as well as C75 treatment. Meanwhile, C75 treatment reversed hypoxia-induced oxidative stress and activated PI3K/AKT signaling. shRNA-mediated inhibition of FAS reduced its expression and oxidative stress levels and improved mitochondrial respiratory capacity and ATP levels of hypoxia-induced HPASMCs. Conclusions . Inhibition of FAS plays a crucial role in shielding mice from hypoxia-induced PAH, which was partially achieved through the activation of PI3K/AKT signaling, indicating that the inhibition of FAS may provide a potential future direction for reversing PAH in humans.